Spoken from the Heart - Bush, Laura Welch 1946- (New York : Scribner, 2010)
In a candid memoir, the former first lady discusses the frantic and fearful months after September 11th, her trip to Afghanistan, her advocacy on behalf of women in oppressed countries, her love of libraries, and what really happens in the White House.
Includes bibliographical references (p. 439-441) and index.
Keywords: Bush, Laura Welch, -- 1946-; Presidents' spouses -- Biography -- United States